New aspects of the surface chemistry of sulfur on Au(111): Surface structures formed by gold-sulfur complexes - Carro, Pilar (2019)
Sulfur adsorption on gold surfaces has been extensively studied because of the key role of sulfur species in heterogeneous catalysis, and, more recently, due to the interest in the synthesis of anisotropic gold nanoparticles with potential applications in medicine that involves sulfide reduction. Here we report new surface structures for sulfur on Au(111) by combining in situ scanning tunneling microscopy in aqueous sodium sulfide solutions and density functional theory calculations. Our results show two related lattices, (3√3 × 3√3) R30° (θ = 0.22) and (√7 × √7) R19.1° (θ = 0.57), that involve AuS3 complexes as building blocks. Gold‑sulfur complexes are formed by the lifting of gold atoms from the substrate surface as revealed by density functional theory calculations. These species, intermediate between adsorbed S in the well-known (√3 × √3)-R30○ lattice and adsorbed polysulfides in organized rectangular structures, explain the surface coverage of gold vacancy islands, a fingerprint of S adsorption on Au(111).